Outcome of bridge to surgery stenting for obstructive left colon cancer. Issue 12 (8th April 2016) - Kim, Min Ki; Kye, Bong‐Hyeon; Lee, In Kyu; Oh, Seong Taek; Ahn, Chang Hyeok; Lee, Yoon Suk; Lee, Sang Chul; Kang, Won‐Kyung
Abstract : Background: The aim of our study was to compare short‐ and long‐term outcomes of stent insertion followed by surgery with those of emergency surgery for left colon malignant obstructions. Methods: The medical records of patients who received curative resection due to obstructive primary left colon cancer and who were diagnosed with stage II or III from January 2004 to December 2010 in six hospitals affiliated with The Catholic University of Korea were reviewed. One hundred and twelve patients in self‐expandable metallic stent (SEMS) group were matched to 56 patients in the emergency surgery (ES) group using propensity score matching method. Overall survival (OS) and disease‐free survival (DFS) were compared between the groups. Perioperative outcomes and pathologic results were also compared. Results: Baseline characteristics were comparable between the two groups after matching. The analysis of perioperative outcomes showed short‐term advantages of stent insertion. Patients in the SEMS group were more likely (87.5 versus 75.0%, P  = 0.049) to have a distal resection margin >5 cm. Harvesting ≥12 lymph nodes were more frequent (89.3 versus 71.4%, P  = 0.007) in the SEMS group. Five‐year DFS was 69.5% in the SEMS group and 73.1% in the ES group ( P  = 0.464). Five‐year OS was not different between the groups (79.7 versus 77.7%, P  = 0.989). Conclusions: SEMS can be a reasonable therapeutic option for malignant obstruction in patients with left colon cancer until definitive conclusion about the long‐term survival effect of SEMS is made from further large‐scale prospective randomized trials.